ANALISIS SOSIOLOGI SASTRA DALAM NOVEL SABALAKANA KARYA DADAN SUTISNA - Ayang Satria Aditya Dermawan; Fajar Sukma Nur Alam (Universitas Batanghari, 2026)
The purpose of this study is to describe the sociology of literature in Dadan Sutisna's Novel Sabalakana. This research method uses descriptive analysis and data collection techniques using note-taking techniques. The instrument used is a data card. The results of the research on the sociology of literature in the Novel Sabalakana include: a) 10 sociologies of the author (description of social reality and the mindset of society, description of his reaction to the influence of modern culture, views on the important role of women in history and social dynamics, views on social relations, traditional values that embrace virtue and love, how society faces life's trials, traditional society's views on revenge, power, and fear can hinder the function of the media as a source of information, the importance of social ethics not to interfere in personal affairs, and the author's depiction of socio-political criticism of freedom of expression in society); b) 6 sociologies of literary works (the relationship between literature and society, socio-cultural background, social structure and power, social conflict, social criticism, and moral values and messages); c) 4 sociologies of readers and 4 impacts of literary works (sociology of readers: general readers, critical readers, non-Sundanese readers, and emotional responses of readers); and (social impact of literary works: teaching social criticism, including political awareness, developing cultural discussions, and increasing appreciation of Sundanese literature).